The rise and fall of an ancient Adelie penguin 'supercolony' at Cape Adare, Antarctica - Emslie, Steve; Mckenzie, Ashley; Patterson, William (IEDA: US Antarctic Program Data Center, 2020)
Abstract: We report new discoveries and radiocarbon dates on active and abandoned Adélie penguin (Pygoscelis adeliae) colonies at Cape Adare, Antarctica. This colony, first established at approximately 2000 BP (calendar years before present, i.e. 1950), is currently the largest for this species with approximately 338 000 breeding pairs, most located on lowlying Ridley Beach. We hypothesize that this colony first formed after fast ice began blocking open-water access by breeding penguins to the Scott Coast in the southern Ross Sea during a cooling period also at approximately 2000 BP. Our results suggest that the new colony at Cape Adare continued to grow, expanding to a large upper terrace above Ridley Beach, until it exceeded approximately 500 000 breeding pairs (a 'supercolony') by approximately 1200 BP. The high marine productivity associated with the Ross Sea polynya and continental shelf break supported this growth, but the colony collapsed to its present size for unknown reasons after approximately 1200 BP. Ridley Beach will probably be abandoned in the near future due to rising sea level in this region. We predict that penguins will retreat to higher elevations at Cape Adare and that the Scott Coast will be reoccupied by breeding penguins as fast ice continues to dissipate earlier each summer, restoring open-water access to beaches there.